Application of spheroidal agglomerates of Î³-Al2O3 in the fluoride removal from aqueous medium - Romero Toledo, Rafael; Ruiz Santoyo, Víctor; Zurita Luna, Ulises; Rangel Porras, Gustavo; Martínez Rosales, Merced (Acta Universitaria, 2019)
A spheroidal agglomerate γ-Al2O3 adsorbent obtained from pseudoboehmite for effective removal of fluoride from aqueous medium was investigated in the present study. The surface properties were characterized by several techniques: XRD, physisorption of N2, FE-SEM/EDS, 27Al NMR, FT-IR Pyridine adsorption, PZ and particle size. Batch experiments were conducted and they were compared with a commercial activated alumina (AA). The process was carried out at pH 5, 7, and 9, then at 25 and 35 ºC. Batch experimental results indicated that the spheroidal agglomerates of γ-Al2O3 remove up to 15 mg/g with a higher adsorption capacity than AA of 13 mg/g, at pH 5, studied at 25 and 35 °C. The F− adsorption processes in γ-Al2O3 and AA followed the pseudo-first-order kinetics and the Langmuir isotherm. The results showed an adsorbent effective for removal of F−.